Religious Nationalism: Narendra Modi’s 2019 Election Victory Speech - Nihar Sreepada (Religions)
The ideology of nationalism is permeating and ascending across societies, eventually manifesting materially in several nations across the world. In this essay, I analyze the religious manifestation of nationalism within the context of India’s Hindu nationalism. I argue that Modi, in his 2019 election victory speech, constructs a grand narrative of Hindu nationalistic unification by positioning himself as a Hindu sanyasi (ascetic) and by alluding to Hindu mythologies. First, I present the historical context of India’s Hindu nationalism (Hindutva). Second, I explicate the formation of an ideological discourse through Kenneth Burke’s focus on identification and the constitutive rhetoric of calling into being the second and third persona. Third, I critique the ideological formations of Modi’s speech for its grand narrative of Hindu nationalistic unification. Fourth, I conclude within a broader context of national collective imaginings and the ideological formations of nationalistic rhetoric.